Laporan Diagnosis Komunitas: Pencegahan Ispa Balita di Puskesmas Sindang Jaya, Tangerang, Banten (12 Februari - 14 Maret 2025) - Siriwa, Thalia Gabriella; Ernawati, Ernawati; Tanuwijaya, Agnes Stephanie; Indra, Dennis Onesimus; Khamila , Shifa (Syntax Literate, 2025)
Acute Respiratory Tract Infection (ARI) is an infectious disease that attacks the upper or lower respiratory tract acutely, with a significant impact on toddlers. Toddlerhood is a crucial period for a child's growth and development, which affects the success of future development. WHO data in 2020 recorded 4.25 million deaths due to ISPA per year, while in Indonesia, the Health Office recorded 705,659 deaths (39.2%) due to ISPA in 2020. In Banten Province, the prevalence of ISPA in the 1-4 year age group reached 4.9%, with the Sindang Jaya Health Center reporting 1,190 cases in 2023 and 2,284 cases in 2024. This report aims to reduce the incidence of ISPA in toddlers in the Sindang Jaya Health Center area, Tangerang Regency. Identify problems using Blum's Paradigm and prioritize problems with the Delphi method. The root cause of the problem is analyzed with the Fishbone diagram, including knowledge, attitudes, and behaviors. The intervention was carried out in the form of ISPA counseling, cough etiquette training, and 6-step handwashing training on March 1, 2025, with 20 participants. As a result, all participants increased their knowledge and were able to practice coughing etiquette and washing hands properly. Successful interventions, with lifestyle being an important factor in the increase in ISPA cases.